Digital Platform Utilization and ICT Literacy on Global Market Access among MSMEs: The Mediating Role of Digital Business Readiness and the Moderating Effect of Government Support - Nurfaizal, Yusmedi; Kurniawan, Arief Adhy; Hermawan, Hellik; Surya Saputra, Dhanar Intan; Amalina, Siti Nahla; Hafshah, Luqyana Nida (Journal of Applied Data Sciences, 2025)
This study investigates how digital capabilities and institutional support shape global market access among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, with a specific focus on Banyumas Regency. The research integrates technology adoption, organizational readiness, and policy support into a unified structural model to explain MSME internationalization in semi-urban contexts. The objective is to assess the direct effects of digital platform utilization and ICT literacy on global market access, the mediating role of digital business readiness, and the moderating effect of government support. A survey of 125 digitally engaged MSMEs was analyzed using Partial Least Squares Structural Equation Modeling. The findings reveal that digital platform utilization (β = 0.163; p = 0.008) and ICT literacy (β = 0.161; p = 0.004) significantly and directly enhance global market access. Both constructs also positively influence digital business readiness digital platform utilization (β = 0.600; p 0.001) and ICT literacy (β = 0.497; p 0.001) which itself contributes to market access (β = 0.154; p = 0.037). Mediation analysis confirms that digital business readiness significantly mediates the relationship between digital capabilities and global market access, with indirect effects of 0.093 (p = 0.045) and 0.077 (p = 0.035) for digital platform utilization and ICT literacy, respectively. Furthermore, government support significantly moderates the effect of digital readiness on market access (β = 0.222; p = 0.002). The model demonstrates strong explanatory power (R² = 0.782 for global market access) and predictive relevance (Q² = 0.507). This study contributes to the digital transformation literature by positioning digital business readiness as a critical enabler of MSME internationalization and highlights the synergistic role of government interventions in amplifying internal digital capabilities. The novelty lies in applying an integrated model to a semi-urban developing economy setting, offering insights for inclusive digital ecosystem design and policy formulation.